The effect of addition of spinach flour (amaranthus sp) on consumer acceptance of catfish ball - Mychael F Naibaho; Dewita Buchari; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The study was intended to examine the effect of spinach flour on consumer acceptance ofcatfish ball. About 36kg catfish was taken from a fish market in Pekanbaru. Four types of fishballs were prepared from catfish meat which was fortificated with 0%, 2,5%, 5%, and 7,5%spinach flour. The catfish balls were evaluated for consumer acceptance and chemicalcomposition. The results indicate that the catfish balls added with 2,5% spinach flour was themost preferable by consumers. The catfish balls contains: 56,78% water, 20,58% protein, 3,08%ash, and 209,80mg calcium.Keyword: Catfish ball, spinach flour, consumer acceptance, chemical composition